The Use of Various Filtaritaion Media in Lowering the Level of Water Hardness - Ferry WF Waangsir; Gede Putu Arnawa; Johannis JP Sadukh; Debora G. Suluh (Postgraduate, University of Mataram, 2023)
Hard water is common in areas with thick topsoil and limestone formations. Because the topography of Kupang City is in the form of limestone, in the rainy season rainwater passes through the limestone soil layer so that the raw water becomes hard or very hard. Identification and analysis of field parameters and levels of raw water hardness before and after treatment to calculate the effectiveness of decreasing hardness of various types of filter media. This research is an experimental study. The object of inspection is raw water from Oenesu springs that have undergone filter media treatment. The filter media consists of activated carbon, silica sand, quartz sand, and zeolite with a residence time of 60 minutes. The results of laboratory tests are displayed in the form of tables and graphs and analyzed. The field parameters tested are smell, taste, color, temperature, turbidity, TDS and pH to meet water quality standards. The level of hardness before and after treatment obtained raw water hardness of 365.33 mg/L, activated carbon media 362.85 mg/L, silica sand media 236.53 mg/L, quartz sand media 239.01 mg/L and zeolite media 296.59 mg/L. The field parameters tested meet water quality standards according to Permenkes 32 of 2017. The level of water hardness treated by the filtration process with quartz sand media is more effective in reducing the level of raw water hardness, with a decrease efficiency of 35.26%.